Catalytic Ethylene Production from Ethanol Dehydration over Non-Modified and Phosphoric Acid Modified Zeolite H-Y (80) Catalysts - Jiah, Chee Soh; Soo, Ling Chong; Cheng, C. K. (Elsevier Ltd, 2017)
The present work reports on the effects of phosphoric acid-modified Zeolites-Y towards the ethylene formation from ethanol dehydration. The catalyst was impregnated with different H3PO4 loadings from 10 to 30wt%. All the catalysts were characterized using N2-physisorption, thermogravimetric analysis, NH3-TPD, FTIR, SEM-EDX, X-ray diffraction and XPS techniques. The non-modified Zeolite-Y with Si/Al 80:1, H-Y (80) was found to exhibit excellent catalytic activity owing to the presence of weak acid sites that was able to protonate the hydroxyl group of ethanol. Although ethanol conversion dropped with phosphorus modified catalysts, it was found that the modified Zeolite-Y with 10wt% H3PO4 can achieve 99% selectivity to ethylene at 723 K and ethanol partial pressure of 16 kPa. Overall, ethanol conversion and ethylene selectivity decreased in the order of H-Y (80)> 10P/H-Y (80) > 20P/H-Y (80) > 30P/H-Y (80). The decrease in ethanol dehydration activity of phosphorus modified catalysts can be ascribed to the reduced BET specific surface area and pore volume due to the surface coverage by layers of H3PO4, consequently, hindered ethanol access to the active site However, the spent phosphorus modified Zeolite-Y catalyst consistently showed less carbon formation compared to the undoped catalyst. This could be due to the reduction in strong acid site and also hindrance of C2H5OH from travelling deep into the pore networks of H-Y (80), therefore reducing the residence time with a consequence of minimizing the carbon laydown.